A valorização das produções culturais das crianças nas mediações pedagógicas do professor de Educação Física na Educação Infantil - Scottá, Bianca Andreatta (2018)
This dissertation aims to study the cultural productions of children in Physical Education classes with Early Childhood Education, focusing on the possibilities that these productions present for the pedagogical mediation of this curricular component with early childhood. The study is organized in such a way that each objective corresponds to a chapter / article, with its own methodology. The chapter on the state of the art uses Bibliographic research to analyze academic-scientific works in the field of Physical Education, which value the cultural productions of children in Early Childhood Education. We adopted the following sources: Annals of Conbrace, scientific journals, dissertations and theses from the area of Physical Education, from 1996 to 2016. In the process of data analysis, we took bibliometric and word cloud indicators, proposed by Iramuteq Software . The following chapter uses Narrative (Auto) Biográfica, to analyze narratives of five Physical Education teachers from the Municipal Network of Vitória / ES, chosen intentionally for this study, who value the cultural productions of children in their classes in Early Childhood Education. In order to enhance the narratives, we adopted "episodes of interaction", sharing prototypical situations in which children's cultural productions were observed, understood and valued in the teachinglearning processes. For the analysis, we establish dialogues between the academic-scientific production, with the pedagogical practices of the teachers that value the manifestations of the children and the theoretical presuppositions defined for this study. As results, we perceive that these fields go in a dialectical way, because the academic-scientific production served as support to interpret the pedagogical practices of teachers and many situations that were described about the process of valorization of the children's cultural productions in the texts analyzed, fact, are being incorporated in the pedagogical practices of the selected teachers. We signal through the episodes, strategies used by teachers to listen and understand children's manifestations. Among them we highlight the dialogical relationship, the re-elaboration of pedagogical intentionality, the arrangement of materials, situations and contexts, the consideration of children's previous experiences, the valorization of their autonomous appropriations and the interpretative reproduction, which subsidized the processes of appropriation, creation and autonomy of children, opening spaces for them to produce culture.